Effect of publishing surgeon-specific outcomes on surgical training. Issue 8 (15th May 2019) - Harries, R L; Glasbey, J; Gokani, V J; Griffiths, G; Allum, W
Abstract: Background: Over the past 10 years, the National Health Service in England has started to publish surgeon-specific outcomes publicly. The aim of this study was to investigate how this has affected training case exposure for surgeons in training. Methods: Anonymized data were collected from the Intercollegiate Surgical Curriculum Programme database for operations in each specialty with published surgeon outcomes, involving surgical trainees on an approved training programme between 1 January 2011 and 31 December 2016. Trainee and supervisor involvement in operations before and after the start of publication of surgeon-specific outcomes were compared using mixed-effects models. Results: A total of 163 076 recorded operative procedures were included. A statistically significant improvement in exposure to training procedures was observed for anterior resection of rectum, carotid endarterectomy, gastrectomy, meningioma excision, prostatectomy and thyroidectomy following the introduction of publication of surgeon outcomes. In coronary artery bypass grafting (CABG) and total hip replacement (THR), however, there was a reduction in involvement in training procedures. This was apparent for both trainee and supervisor involvement in CABG, and for trainee involvement in THR. Conclusion: Exposure to training procedures has improved rather than declined in the UK in the majority of surgical specialties, since the publication of surgeon-specific outcomes. Graphical Abstract: The aim of this study was to investigate how surgeon-specific outcome reporting has affected training case exposure for surgeons in training. Anonymized data were collected from the Intercollegiate Surgical Curriculum Programme database for operations in each specialty with published surgeon-specific outcomes involving surgical trainees on an approved training programme between 1 January 2011 and 31 December 2016. A total of 163 076 recorded procedures showed a statistically significant improvement in exposure to training cases for anterior resection of rectum, carotid endarterectomy, gastrectomy, meningioma excision, prostatectomy and thyroidectomy following the introduction of surgeon-specific outcomes. In coronary artery bypass grafting (CABG) and total hip replacement (THR), however, there was a reduction in involvement in training cases. This was apparent for both trainee and supervisor involvement in CABG, and for trainee involvement in THR. Surprisingly, improves access to training